2015
DOI: 10.1002/adfm.201504014
|View full text |Cite
|
Sign up to set email alerts
|

Highly Connected Silicon–Copper Alloy Mixture Nanotubes as High‐Rate and Durable Anode Materials for Lithium‐Ion Batteries

Abstract: achieved after 1000 cycles at 3.4 A g −1 (or 20 A g −1 ), with a capacity retention rate of ≈84% (≈88%), without the use of any binder or conductive agent. Remarkably, they can survive an extremely fast charging rate at 70 A g −1 for 35 runs (corresponding to one full cycle in 30 s) and recover 88% capacity. This novel alloy-nanotube structure could represent an ideal candidate to fulfi ll the true potential of Si-loaded LIB applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 36 publications
(38 reference statements)
0
54
0
Order By: Relevance
“…g) Cycling performance of the Cu‐Si anode with the discharge/charge current of 0.84, 1.6, and 3.2 A g −1 over 100 cycles, respectively. Reproduced with permission . Copyright 2016, John Wiley & Sons, Inc.…”
Section: Methods Of Surface and Interface Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…g) Cycling performance of the Cu‐Si anode with the discharge/charge current of 0.84, 1.6, and 3.2 A g −1 over 100 cycles, respectively. Reproduced with permission . Copyright 2016, John Wiley & Sons, Inc.…”
Section: Methods Of Surface and Interface Engineeringmentioning
confidence: 99%
“…Copper, with an excellent conductivity, also has been widely used as the metallic coating layer on silicon‐based anodes . Song et al indicated a template‐free and binder‐free synthesis of highly connected and hollow silicon‐copper nanotubes for high‐rate and durable LIBs . The crossing CuO nanowires were firstly growth on the copper foam substrate by a thermal oxidation treatment.…”
Section: Methods Of Surface and Interface Engineeringmentioning
confidence: 99%
“…However, the high reactivity between lithiated M and O 2 on the interface of the anode and the electrotype triggers additional irreversible reaction, thus resulting in large irreversible loss of lithium ions and rapid attenuation of capacity. In addition, many problems must be addressed to facilitate their further applications in Li–O 2 batteries; nonetheless, many exciting breakthroughs, including high specific capacity, long‐term cycle lifespan, and fast charging rates, have been achieved for nanostructured M (M = Si, Ge, Sn, Al) anodes . For example, a high specific surface area of nanostructured Li x Si (or Li x Sn) anodes will strengthen the reactivity caused by Li x Si (or Li x Sn) and O 2 , which further leads to increased irreversible capacity loss and lowered Coulombic efficiency during the charge/discharge cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Si nanotubes (Si NTs) are another promising kind of 1D Si components with intrinsic void spaces, with which high‐performance C–Si hybrids have been intensively demonstrated as well for LIB . For examples, Lu et al fabricated carbon decorated Si nanotubes (C@SiNTs) by chemical vapor deposition .…”
Section: Dimensional Design Upon Nano‐simentioning
confidence: 99%